2016
DOI: 10.4000/quaternaire.7543
|View full text |Cite
|
Sign up to set email alerts
|

Enregistrements sédimentaires d’événements de haute énergie, exemples de la côte atlantique de Rabat-Skhirat (Maroc)

Abstract: Des dépôts holocènes de nature événementielle ont été identifiés sur le secteur littoral des environs de Rabat-Skhirat (NO du Maroc). A El Harhoura, le massif de calcarénites pléistocènes porte une formation dunaire meuble de 2 m d'épaisseur. Cette formation couvre un dépôt limono-argileux résiduel et elle est constituée par une succession de dépôts sableux massifs superposés ou emboités pouvant contenir des mégablocs. Ces unités attestent de dépôts événementiels holocènes, de type tempête ou tsunami. L'âge de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…On the Moroccan Atlantic coast, this event (E13/14) could be contemporaneous to marine deposits identified by Mhammdi et al, (2015) on the Loukkos estuary with an estimated mid-Holocene age, and by Chahid et al, (2016) on the Rabat-Skhirat 20 coast with an age between 2700 and 2200 cal BP.…”
Section: Correlation Of Dated Events With Other Historical Archivessupporting
confidence: 70%
See 1 more Smart Citation
“…On the Moroccan Atlantic coast, this event (E13/14) could be contemporaneous to marine deposits identified by Mhammdi et al, (2015) on the Loukkos estuary with an estimated mid-Holocene age, and by Chahid et al, (2016) on the Rabat-Skhirat 20 coast with an age between 2700 and 2200 cal BP.…”
Section: Correlation Of Dated Events With Other Historical Archivessupporting
confidence: 70%
“…Conversely, only a few studies have been conducted on the Moroccan Atlantic coast (Chahid et al, 2016;Leorri et al, 2010;5 Mhammdi et al, 2015;El Talibi et al, 2016). In this context, the present work aims to reconstruct past marine submersion events from geological archives (cores) collected in Tahaddart estuary (NW of Morocco) using a high-resolution sedimentological and geochemical analysis.…”
Section: Introductionmentioning
confidence: 99%
“…This Harhoura section is also characterized by the presence of several clusters of boulders, which reinforces the event-driven aspect of the deposits that form this section. 14 C dating, performed on this section, places these high-energy deposits between 9900 and 2200 cal BP (Chahid et al 2016). The second section is located in Skhirat, north of the mouth of the Cherrat river.…”
Section: Rabat-bouznika Coastmentioning
confidence: 89%
“…Another work carried out by Chahid et al (2016) in the Rabat-Bouznika area revealed the presence of other high-energy deposits (10-16 in Fig. 6c).…”
Section: Rabat-bouznika Coastmentioning
confidence: 90%
“…1). They are represented in the form of (1) mega-blocks, also known as boulderite deposits, spread over the beaches of Larache (Mhammdi et al 2015), Rabat-Skhirat (Mhammdi et al 2008;Medina et al 2011), Sidi Moussa (Mellas 2012) and Safi (Theilen-Willige et al 2013), (2) or as fine sediment (typically sand size) over the coast of Rabat-Skhiratte and Tahaddart (Chahid et al 2016;El Talibi et al 2016), the lagoons of Oualidia-Sidi Moussa (Leorri et al 2010;Mellas 2012) and the Loukous estuary (Mhammdi et al 2015). Despite these efforts, the majority of these sedimentary deposits lack chronological data, which makes it difficult to know the events responsible for their establishment.…”
Section: Introductionmentioning
confidence: 99%